Multivariate Analysis in the Maximum Strength Performance - de Souza, E. O.; Tricoli, V.; Paulo, A. C.; Silva-Batista, C.; Cardoso, R. K.; Brum, P. C.; Bacurau, A.V. N.; Laurentino, G.; Neves-Jr, M.; Aihara, A. Y.; Ugrinowitsch, C. (International Journal of Sports Medicine, 2012)
This study performed an exploratory analysis of the anthropometrical and morphological muscle variables related to the one-repetition maximum (1RM) performance. In addition, the capacity of these variables to predict the force production was analyzed. 50 active males were submitted to the experimental procedures: vastus lateralis muscle biopsy, quadriceps magnetic resonance imaging, body mass assessment and 1RM test in the leg-press exercise. K-means cluster analysis was performed after obtaining the body mass, sum of the left and right quadriceps muscle cross-sectional area (∑CSA), percentage of the type II fibers and the 1RM performance. The number of clusters was defined a priori and then were labeled as high strength performance (HSP1RM) group and low strength performance (LSP1RM) group. Stepwise multiple regressions were performed by means of body mass, ∑CSA, percentage of the type II fibers and clusters as predictors’ variables and 1RM performance as response variable. The clusters mean±SD were: 292.8±52.1 kg, 84.7±17.9 kg, 19 249.7±1 645.5 mm2 and 50.8±7.2% for the HSP1RM and 254.0±51.1 kg, 69.2±8.1 kg, 15 483.1±1 104.8 mm2 and 51.7±6.2%, for the LSP1RM in the 1RM, body mass, ∑CSA and muscle fiber type II percentage, respectively. The most important variable in the clusters division was the ∑CSA. In addition, the ∑CSA and muscle fiber type II percentage explained the variance in the 1RM performance (Adj R2=0.35, p=0.0001) for all participants and for the LSP1RM (Adj R2=0.25, p=0.002). For the HSP1RM, only the ∑CSA was entered in the model and showed the highest capacity to explain the variance in the 1RM performance (Adj R2=0.38, p=0.01). As a conclusion, the muscle CSA was the most relevant variable to predict force production in individuals with no strength training background.
Keywords: 1RM; muscle biopsy; cross-sectional area; body mass